Photophysical Properties of Fluorescent Probe Thioflavin T in Crowded Milieu - Natalia P. Rodina; Maksim I. Sulatsky; Anna I. Sulatskaya; Irina M. Kuznetsova; Vladimir N. Uversky; Konstantin K. Turoverov (Journal of Spectroscopy)
Thioflavin T (ThT) is a widely used fluorescent probe of amyloid fibrils, which accompanies many serious neurodegenerative and other diseases. Until recently, examinations of processes of amyloid fibril formation in vitro were conducted in solutions whose properties were significantly different from those found inside the densely packed cells. Such crowded cellular milieu is typically simulated in vitro using concentrated solutions of inert polymers, which do not usually interact with proteins. However, these crowding agents can have a direct effect on the ThT molecule, and this effect must be taken into account. We examined the influence of PEG-400, PEG-12000, and Dextran-70 on the photophysical properties of ThT. It was shown that these crowding agents caused the red shift of the absorption, fluorescence excitation, and fluorescence spectra of ThT. Under these conditions, the increases of the molar extinction coefficient, fluorescence quantum yield, and excitation lifetime of ThT are also observed. However, these changes are significantly less pronounced than those observed for ThT bound to fibrils. It is concluded that, despite some effects of crowding agents on intrinsic fluorescent properties of ThT, this dye can be used as a probe of structure and formation of amyloid fibrils in crowded milieu in vitro.